COST 732 in practice: the MUST model evaluation exercise. (18th February 2011) - Sabatino, Silvana Di; Buccolieri, Riccardo; Olesen, Helge R.; Ketzel, Matthias; Berkowicz, Ruwim; Franke, Jorg; Schatzmann, Michael; Schlunzen, K.; Leitl, Bernd; Britter, Rex; Borrego, Carlos; Costa, Ana; et al.
The aim of this paper is to describe the use of a general methodology tailored to the evaluation of micro-scale meteorological models applied to flow and dispersion simulations in urban areas. This methodology, developed within COST 732, has been tested through a large modelling exercise involving many groups across Europe. The major test case used is the Mock Urban Setting Test (MUST) experiment representing an idealised urban area. It is emphasised that a full model evaluation is problem-dependent and requires several activities including a statistical validation that requires a careful choice of the metrics for the comparison with measurements.